Pendampingan Guru PAI dalam Edukasi Lingkungan untuk Kebiasaan Bersih Siswa SDN Sumbersari 1: Pendampingan Guru PAI dalam Edukasi Lingkungan untuk Kebiasaan Bersih Siswa SDN Sumbersari 1 - Muchammad Lubbil Khobir (Journal of Research and Community Service, 2025)
This community service program aims to increase the environmental hygiene awareness of SDN Sumbersari 1 students through a Participatory Action Research (PAR) approach by involving PAI teacher assistance to integrate Islamic values with environmental practices. As an Adiwiyata school at the Pasuruan district level that has a strong culture of gotong royong, this program utilizes local wisdom through three phases: education (integrating verses of the Qur'an and Hadith) about cleanliness in learning, action (conducting Clean Saturday movements, recycling projects, and greening), and reflection (evaluating changes through group discussions). The results showed a significant increase of 82% of students consistently throwing garbage in its place, while 78% showed an increase in collective responsibility through classroom-based environmental projects. A swot analysis identified teacher authority in conveying Islamic values, school leadership support, and local partnerships as key strengths. The study concludes that the combination of religious value-based education with practical activities is effective in fostering sustainable clean habits. Recommendations include further teacher training, development of teaching modules on STEAM-based recycling, and institutionalization of the program through local teacher networks. This model can be replicated in other schools to strengthen religious value-based environmental conservation.